2021
DOI: 10.3390/antiox11010076
|View full text |Cite
|
Sign up to set email alerts
|

Adaptative Up-Regulation of PRX2 and PRX5 Expression Characterizes Brain from a Mouse Model of Chorea-Acanthocytosis

Abstract: The peroxiredoxins (PRXs) constitute a ubiquitous antioxidant. Growing evidence in neurodegenerative disorders such as Parkinson’s disease (PD) or Alzheimer’s disease (AD) has highlighted a crucial role for PRXs against neuro-oxidation. Chorea-acanthocytosis/Vps13A disease (ChAc) is a devastating, life-shortening disorder characterized by acanthocytosis, neurodegeneration and abnormal proteostasis. We recently developed a Vps13a−/− ChAc-mouse model, showing acanthocytosis, neurodegeneration and neuroinflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Although a partial restoration of the actin cytoskeleton was observed in red blood cells, the lack of improvement of neurological symptoms was noted after six-month drug administration [123]. Further, studies on mice models revealed that the drug tested, dasatinib, is not able to cross the blood-brain barrier, but another potential kinase inhibitor, nilotinib, can do that and improve not only haematological but also neurological defects in mice [124,125]. Since the variety of potential treatments is very limited, there is a great need for new drug candidates which could be effective in ChAc patients.…”
Section: Calcium Signalling As a Potential Target For Drug Interventi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a partial restoration of the actin cytoskeleton was observed in red blood cells, the lack of improvement of neurological symptoms was noted after six-month drug administration [123]. Further, studies on mice models revealed that the drug tested, dasatinib, is not able to cross the blood-brain barrier, but another potential kinase inhibitor, nilotinib, can do that and improve not only haematological but also neurological defects in mice [124,125]. Since the variety of potential treatments is very limited, there is a great need for new drug candidates which could be effective in ChAc patients.…”
Section: Calcium Signalling As a Potential Target For Drug Interventi...mentioning
confidence: 99%
“…Newly identified potential repurposable drugs which are effective in alleviating defects of yeast mutant cells, such as calcineurin inhibitors, flavonoids and copper ionophores, require intensive studies using available human cell and mouse models. HeLa siVPS13A [83], fibroblasts or red blood cells from patients and patient-derived neuronal cell models [211] together with a mouse model of ChAc [124] will help to answer the question of whether any of these drugs can be of use for intervention in ChAc and other VPS13-related diseases.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%